Measurement of Wide-Aperture X-ray Beam Trasverse Proﬁle Based on Multiangular Wire Scanning - Stuchebrov S. G. Sergey Gennadevich; Bulavskaya A. A. Angelina Aleksandrovna; Cherepennikov Yu. M. Yuriy Mihaylovich; Miloichikova I. A. Irina Alekseevna (Applications of Monochromatic X-ray, [gamma]-ray, 2019)
Title screen